Selection of promotional media with the integration of AHP Fuzzy and TOPSIS (case study in a study program) - Masrul Indrayana; Dutho Suh Utomo (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2022)
Private universities need new students as one of the income to be able to run their operations. For that promotion needs to be done by them. When carrying out promotional activities, it is necessary to look at the availability of the budget, so it is necessary to be selective and choose the right promotional media and according to the budget. Selection of promotional media in addition to considering the budget, there are several criteria that must be considered, therefore the selection requires a multi-criteria method, one of which is TOPSIS. Initial weighting of the criteria for TOPSIS can be done with Fuzzy AHP, this method is used because it can overcome the fuzzy assesment when performing pairwise comparisons. So far, there are not many combined applications of Fuzzy AHP and TOPSIS in the selection of promotional media, so this research is expected to have a contribution to fill the gap. From the results of the study, it was found that the order of criteria that were important for the study program in the selection of promotional media were; cost, reach, audience fit and easy to apply. Meanwhile, the result of selecting the best promotional media for this study program was through social media